Sources and Countermeasures of Students’ Anxiety in Oral Examination – Take the IELTS speaking test for example - Jingwen Dai (SHS Web of Conferences, 2023)
As English teaching in China has always been "cramming method", students’ shortcomings with oral English make them become anxious. Based on the three sources of anxiety —— the familiarity of the text content, the language proficiency level and feedback from others, this study has conducted semistructured interviews on six IELTS candidates and tried to summarize the countermeasures to overcome anxiety proposed by the interviewees, aiming at helping IELTS candidates reduce their anxiety about the oral test and providing certain reference value for future research on traditional oral English teaching.